Pengaruh Manajemen Keuangan Dan Gaya Hidup Terhadap Aktivitas Belanja Online Mahasiswa Pendidikan Ekonomi Angkatan 2022-2023 Universitas Jambi - Elisa Pitri Situmeang; Refnida; Fadilla Ulfah (JOURNAL OF SHARIA ECONOMICS, 2025)
This study aims to analyze the influence of financial management and lifestyle on online shopping activities among Economic Education students of the 2022–2023 cohorts at Universitas Jambi. The rapid development of digital technology has significantly transformed students’ consumption behavior, where online shopping has become part of a modern lifestyle that emphasizes convenience and efficiency. However, this convenience also has the potential to trigger consumptive behavior, especially among students with inadequate financial management skills. This research employs a quantitative approach using a survey method through questionnaires distributed to respondents. The independent variables in this study are financial management and lifestyle, while the dependent variable is online shopping activity. Preliminary findings indicate that some students are not accustomed to budgeting, recording expenses, and are easily influenced by promotions, trends, and social media in making online purchases. A consumptive lifestyle further strengthens the intensity of online shopping behavior among students. Theoretically, this study is based on the Theory of Planned Behavior and the Theory of Consumption Values, which explain that consumer behavior is influenced by psychological, social, and consumption value factors. Therefore, this research is expected to provide empirical insights into the importance of financial management and lifestyle control in reducing consumptive behavior among students in the digital era